NEW POSSIBILITIES FOR DETERMINING AGE SPECTRA OF 40AR/39AR BY MEANS OF LASERS - Ivanenko V.V.; Karpenko M.I. (My University, 1987)
The present paper describes a method of local laser-aided determination of the degree of disruption of the K-Ar system of the specimen. To combine the advantages of the age spectrum method with the localized character of laser analysis, the properties of the laser beam itself are used: when laser light interacts with dielectrics, the generation of defects in semitransparent and transparent specimens is promoted by absorption of radiation by defects in the material, both external and internal. The proposed method involves a series of layer-by-layer laser irradiations of the same microarea of the specimen in order to identify this nonuniformity. If the specimen is 'too young' because it has lost part of its radiogenic argon, the first laser pulse evaporates the surface layer low in 40Ar. The second pulse, directed into the same crater, evaporates a deeper layer, and so on. Layer-by-layer laser irradiation of a microarea can be used to identify the depthwise inhomogeneity of the distribution of the isotopic 40Ar/39Ar ratio in the specimen. The use of a pulsed laser permits local analysis, since the brevity of the pulse prevents heating of neighboring zones of the specimen.